Characteristics of Bentonite Anti-Impurity Liquid Bath Soap - Emi Erawati; Anisa ur Rahmah; Safira Rijka Ardima; Syahrani Shabrina Dewantari (JST (Jurnal Sains dan Teknologi), 2026)
Contact between human skin and a source of uncleanliness, such as dog saliva, requires a special purification method. The addition of bentonite as a substitute for clay in soap preparations makes the washing process more practical. The purpose of this study was to analyse the characteristics of anti-impurity liquid bath soap from bentonite. Data analysis in this study was conducted using a non-factorial Randomised Block Design (RBD) approach. This study was conducted by varying the ratio of bentonite to glycerin (3:10, 4:9, and 5:8 w/w), stirring speed (200, 400, and 600 rpm), sucrose solution concentration (20, 30, and 40% w/v), and stirring time (30, 45, and 60 minutes). The formulation of the soap preparation must be adjusted to meet the quality standards for liquid bath soap, including pH, viscosity, specific gravity, foam height, free fatty acid content, and total plate count for microbial contamination. Based on the research results, the optimal bentonite-to-glycerin ratio was 5:8 (w/w), the stirring speed was 200 rpm, the sucrose solution concentration was 20% (w/v), and the stirring time was 45 or 60 minutes. From the research results, the pH value was also obtained, ranging from 8.17 to 10, viscosity was 500 to 1226 cPs, specific gravity was between 1.01 and 1.05 g/mL, foam height was 74.73 – 89.34 mm, free fatty acid value was ranging from 0.56 2.49%, and the total plate count value of microbial contamination was 0 colonies/mL. The implications of this research can serve as a reference for developing anti-impurity liquid bath soap under optimal formulation and operating conditions, thereby producing high-quality products.